New records of suctorians (Ciliophora: Suctoria) as epibionts of aquatic true bugs (Hemiptera: Prosorrhyncha: Nepomorpha) from two regions: Mexico and Eastern Europe - Mariño-Pérez, Ricardo; Dovgal, Igor; Mayén-Estrada, Rosaura (Zootaxa, 2011)
Here, we provide new records of suctorians (Ciliophora: Suctoria), epibionts of aquatic true bugs (Hemiptera: Prosorrhyncha: Nepomorpha) collected in Ukraine, Belarus and Mexico. The worldwide distribution of the 16 species we found is updated, from which, 15 species are new records as epibionts of 15 species of aquatic true bugs. Only for the suctorian Discophrya gessneri Matthes, we confirm the previous record (epibiont of Aphelocheirus aestivalis Fabricius). We conclude that the relationship between the suctorians and aquatic true bugs is poorly studied and some suctorian genera (Dis- cophrya Lachmann and Periacineta Collin) inhabit as nepomorphans as other aquatic insects (Coleoptera). However the high degree of specificity at the species level of these genera is evident, for which we provide some possible explanations according to the group of basibiont.